ChemInform Abstract: Eight New Diterpenoids and Two New Nor‐Diterpenoids from the Stems of Croton cascarilloides. Issue 38 (30th August 2013) - Kawakami, Susumu; Toyoda, Hiroki; Harinantenaina, Liva; Matsunami, Katsuyoshi; Otsuka, Hideaki; Shinzato, Takakazu; Takeda, Yoshio; Kawahata, Masatoshi; Yamaguchi, Kentaro
Abstract isolation and structure determination of eight new diterpenoids, named crotocascarins A‐H (I) and (II), and two new nor‐diterpenoids, named crotocascarins α (IIIb) and β (IIIa)